ENGLISH WORDPLAY TRANSLATION INTO INDONESIAN IN THE SUBTITLE OF AMERICAN TELEVISION SERIES - Fithri, Ayyuhatsanail (Journal of Language and Literature, 2019)
One of the humorous aspects in the field of language is wordplay. Wordplay tends to create linguistic problems of translability due to the the diversity of languages and different linguistic typology. However, recently a number of movies and series from overseas which the genre is comedy must contain wordplay in the subtitles. Whilst, the subtitles in one of the scope of audiovisual translation, it requires several techniques to translate as subtitling adds space, time, and presentation. This paper is to investigate types of wordplay found in the subtitles of Hannah Montana and strategies applied to translate English wordplay into Indonesian. The data of this study was collected from an American series entitled Hannah Montana from season one to three. Hence, the most appropriate method employed is qualitative. The sampling technique applied is purposive sampling. The total four types of wordplay found in the series, namely: phonological and graphological structure (consists of homonymy, paronymy, and homophony), lexical structure (polysemy), morphological structure, and syntactic structure. Most of the translator whom sub movies or series used is wordplay to non-wordplay strategy. This strategy has a significant effect in rendering the meaning to the target text that affects the audience when they watch the film whether to laugh or not to laugh.